2020
DOI: 10.1038/s41467-020-19004-4
|View full text |Cite|
|
Sign up to set email alerts
|

Enabling “lithium-free” manufacturing of pure lithium metal solid-state batteries through in situ plating

Abstract: The coupling of solid-state electrolytes with a Li-metal anode and state-of-the-art (SOA) cathode materials is a promising path to develop inherently safe batteries with high energy density (>1000 Wh L−1). However, integrating metallic Li with solid-electrolytes using scalable processes is not only challenging, but also adds extraneous volume since SOA cathodes are fully lithiated. Here we show the potential for “Li-free” battery manufacturing using the Li7La3Zr2O12 (LLZO) electrolyte. We demonstrate that L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
181
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(196 citation statements)
references
References 38 publications
4
181
2
Order By: Relevance
“…Generally, although the separation process is believed to damage Na metal itself, the spatial distribution, architecture, and dimensions of the cycled Na are expected to be preserved. [ 42 ] As demonstrated in Figure 4 a,b, the metallic Na of cycled Na/NASICON/Na cell shows distinct ridges and cracks on its surface. The Energy Dispersive Spectrometer spectrum (Figure S13, Supporting Information) only shows the peaks of Na, O, and C, indicating that no SSE impurity is counted.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, although the separation process is believed to damage Na metal itself, the spatial distribution, architecture, and dimensions of the cycled Na are expected to be preserved. [ 42 ] As demonstrated in Figure 4 a,b, the metallic Na of cycled Na/NASICON/Na cell shows distinct ridges and cracks on its surface. The Energy Dispersive Spectrometer spectrum (Figure S13, Supporting Information) only shows the peaks of Na, O, and C, indicating that no SSE impurity is counted.…”
Section: Resultsmentioning
confidence: 99%
“…[8,21,22] Li metal is an ideal anode that is hoped to be enabled by the development of all-solid-state technologies. [3,[23][24][25][26][27][28][29] Nirich layered oxides, LiMO 2 (M = Ni, Co, Mn, Al), which have been extensively investigated as cathodes for advanced LIBs based on LEs, [30][31][32][33][34][35][36] are also strong candidates for integration into practical ASLBs at scale. [18,37,38] Despite the use of SEs showing high Li + conductivities (>10 −3 S cm −1 ), electrochemical performances of layered oxide cathodes including LiCoO 2 and Li[Ni,Co,Mn]O 2 in ASLB cells have not been satisfactorily high in most previous reports.…”
Section: Introductionmentioning
confidence: 99%
“…[14] All the abovementioned limitations can be overcome or reduced if dendrite growth/breakage can be prevented during the deposition/ dissolution process. Many studies have been reported on the construction of dendrite-free metal anodes: a) fabrication of modified electrodes or metal substrate surfaces, [15][16][17][18][19][20][21][22][23][24] b) synthesis of new electrolytes, [25][26][27][28][29] c) use of solid electrolytes, [22,[30][31][32] and d) improvement of the electrode-electrolyte interface. [9,15,33,34] However, these studies have rarely focused on the properties, such as the stability of dendrites during charging and discharging, of dendrites.…”
mentioning
confidence: 99%